Hubungan antara Brand Image dan Self Esteem dengan Keputusan Pembelian Produk Kosmetik secara Online - Setyawati, Apriliana Dwi; Pramono, Ridwan Budi (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to examine the relationship between brand image and self esteem with online cosmetic product purchasing decisions. The rapid development of e-commerce has changed consumer behavior, particularly in the beauty industry. This study used a quantitative method involving 100 respondents who frequently purchase cosmetics online, purchasing twice a month. Data collection was conducted using a validated questionnaire, covering the brand image scale, self esteem, and purchasing decisions. The analysis technique used two-predictor regression and product moment. The results showed a significant positive relationship between brand image and self esteem with purchasing decisions. It can be concluded that the more positive the brand image and the higher a person's self esteem, the greater the likelihood of the individual making online cosmetic product purchasing decisions.